Initial Design Strategies and Their Effects on Sequential Model-Based Optimization: An Exploratory Case Study Based on BBOB - Bossek, Jakob; Doerr, Carola; Kerschke, Pascal (Proceedings of the Genetic and Evolutionary Computation Conference)
Sequential model-based optimization (SMBO) approaches are algorithms for solving problems that require computationally or otherwise expensive function evaluations. The key design principle of SMBO is a substitution of the true objective function by a surrogate, which is used to propose the point(s) to be evaluated next. SMBO algorithms are intrinsically modular, leaving the user with many important design choices. Significant research efforts go into understanding which settings perform best for which type of problems. Most works, however, focus on the choice of the model, the acquisition function, and the strategy used to optimize the latter. The choice of the initial sampling strategy, however, receives much less attention. Not surprisingly, quite diverging recommendations can be found in the literature. We analyze in this work how the size and the distribution of the initial sample influences the overall quality of the efficient global optimization (EGO) algorithm, a well-known SMBO approach. While, overall, small initial budgets using Halton sampling seem preferable, we also observe that the performance landscape is rather unstructured. We furthermore identify several situations in which EGO performs unfavorably against random sampling. Both observations indicate that an adaptive SMBO design could be beneficial, making SMBO an interesting test-bed for automated algorithm design.
Keywords: continuous black-box optimization; design of experiments; initial design; sequential model-based optimization

Kant, Linnaeus, and the economy of nature - Wells, Aaron (Studies in History and Philosophy of Science Part C: Studies in History and Philosophy of Biological and Biomedical Sciences)
Keywords: History and Philosophy of Science; History; General Medicine

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

SLA-controlled Proxy Service Through Customisable MANO Supporting Operator Policies - Soenen, Thomas; Vicens, Felipe; Bonnet, José; Parada, Carlos; Kapassa, Evgenia; Touloupou, Marious; Fotopulou, Eleni; Zafeiropoulos, Anastasios; Pol, Ana; Kolometsos, Stavros; Xilouris, George; Alemany, Pol; et al. (2019 IFIP/IEEE Symposium on Integrated Network and Service Management (IM))
Service Level Agreements are essential tools enabling clients and telco operators to specify required quality of service. The 5GTANGO NFV platform enables SLAs through policies and custom service lifecycle management components. This allows the operator to trigger certain lifecycle management events for a service, and the network service developer to define how to execute such events (e.g., how to scale). In this demo we will demonstrate this unique 5GTANGO concept using an elastic proxy service supported by a high availability SLA enforced through a range of traffic regimes.
Keywords: 5G mobile communication; contracts; quality of service; telecommunication traffic; virtualisation; custom service lifecycle management components; lifecycle management events; network service developer; elastic proxy service; SLA-controlled proxy service; customisable MANO; operator policies; Service Level Agreements; unique 5G TANGO concept; 5G TANGO NFV platform; quality of service; traffic regimes; high availability SLA; Monitoring; Probes; Portals; Quality of service; Tools; Servers; Graphical user interfaces

Non-GAAP Reporting and Investor Attention: Are Investors Misled by Exclusions of Recurring Expenses from Non-GAAP Earnings before Restatement Announcements? - Müller, Jens; Sievers, Sönke; Mehring, Oliver; Sofilkanitsch, Christian
Non-GAAP reporting is under debate as managers may opportunistically inflate non-GAAP earnings. By separating firms into groups based on exclusions of recurring expenses before material restatements occur this paper investigates whether market participants are misled based on ex-ante non-GAAP reporting. The results show a decline in cumulative abnormal returns (–11.8% aggressive non-GAAP Reporting vs. –2.7% non-aggressive non-GAAP reporting), reduction in overvaluation (–22.18% vs. no decline) and losses in the earnings response coefficient (–51.8% vs. no significant decline) for firms with prior aggressive non-GAAP reporting. Further, we document that investors are less responsive to aggressively reported non-GAAP earnings ex-post, indicating that increased attention enhances investor’s ability to see through the quality of non-GAAP exclusions.
Keywords: Keywords: non-GAAP reporting; restatements; information content of earnings; firm value; overvaluation

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS spread changes - Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We find that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric five-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline finding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

Differentiability of the evolution map and Mackey continuity - Hanusch, Maximilian (Forum Mathematicum)
Keywords: regularity of Lie groups; differentiability of the evolution map

Joining of high strength aluminum alloys by refill friction stir spot welding (III-1854-18) - Schmal, Christopher; Meschut, Gerson; Buhl, Nico (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; General Chemistry; Bioengineering

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specific, fundamental bank-specific as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We find that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specific, fundamental bank-specific as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We find that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Determinants of CDS trading on major banks - Hippert, Benjamin; Uhde, André
Employing credit default swap (CDS) data for a sample of 52 major banks across 18 countries from 2008 to 2016, this paper investigates determinants of the outstanding net notional amount of CDS which are written on banks. We extend the current literature dealing with CDS trading by analyzing further CDS trading-specifi c, fundamental bank-speci fic as well as macroeconomic and institutional determinants with a focus on bank CDS trading. We fi nd that, next to well-discussed determinants for corporate firms in the literature, especially a bank's tail risk, capital adequacy, loan portfolio and business model affect a bank's outstanding CDS net notional. This finding indicates that investors in the bank CDS market partly have a recourse to a fundamental analysis for their investment decision. Our study fills an important gap since empirical studies have solely focused on sovereign and corporate CDS yet. In addition, the analysis at hand provides important implications for both academics and practitioners since understanding the trading motives of bank CDS investors gives deeper insights into the still opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS-Spread changes - Uhde, André; Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We nd that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric ve-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline nding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Conceptualizing smart service systems - Beverungen, Daniel; Müller, Oliver; Matzner, Martin; Mendling, Jan; vom Brocke, Jan (Electronic Markets)
Recent years have seen the emergence of physical products that are digitally networked with other products and with information systems to enable complex business scenarios in manufacturing, mobility, or healthcare. These “smart products”, which enable the co-creation of “smart service” that is based on monitoring, optimization, remote control, and autonomous adaptation of products, profoundly transform service systems into what we call “smart service systems”. In a multi-method study that includes conceptual research and qualitative data from in-depth interviews, we conceptualize “smart service” and “smart service systems” based on using smart products as boundary objects that integrate service consumers’ and service providers’ resources and activities. Smart products allow both actors to retrieve and to analyze aggregated field evidence and to adapt service systems based on contextual data. We discuss the implications that the introduction of smart service systems have for foundational concepts of service science and conclude that smart service systems are characterized by technology-mediated, continuous, and routinized interactions.
Keywords: Boundary object; Internet of things; Service science; Smart products; Smart service

How to Deal with Inaccurate Service Descriptions in On-The-Fly Computing: Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 23rd International Conference on Natural Language and Information Systems)
The vision of On-The-Fly Computing is an automatic composition of existing software services. Based on natural language software descriptions, end users will receive compositions tailored to their needs. For this reason, the quality of the initial software service description strongly determines whether a software composition really meets the expectations of end users. In this paper, we expose open NLP challenges needed to be faced for service composition in On-The-Fly Computing.
Keywords: Requirements Extraction; Temporal Reordering of Software Functions; Inaccuracy Compensation

Decision Support for the Optimal Coordination of Spontaneous Volunteers in Disaster Relief - Rauchecker, Gerhard; Schryen, Guido (Proceedings of the 15th International Conference on Information Systems for Crisis Response and Management)
When responding to natural disasters, professional relief units are often supported by many volunteers which are not affiliated to humanitarian organizations. The effective coordination of these volunteers is crucial to leverage their capabilities and to avoid conflicts with professional relief units. In this paper, we empirically identify key requirements that professional relief units pose on this coordination. Based on these requirements, we suggest a decision model. We computationally solve a real-world instance of the model and empirically validate the computed solution in interviews with practitioners. Our results show that the suggested model allows for solving volunteer coordination tasks of realistic size near-optimally within short time, with the determined solution being well accepted by practitioners. We also describe in this article how the suggested decision support model is integrated in the volunteer coordination system which we develop in joint cooperation with a disaster management authority and a software development company.
Keywords: Coordination of spontaneous volunteers; volunteer coordination system; decision support; scheduling optimization model; linear programming

Towards a Multi-Stage Approach to Detect Privacy Breaches in Physician Reviews - Bäumer, Frederik Simon; Kersting, Joschka; Orlikowski, Matthias; Geierhos, Michaela (Proceedings of the Posters and Demos Track of the 14th International Conference on Semantic Systems co-located with the 14th International Conference on Semantic Systems (SEMANTiCS 2018))
Physician Review Websites allow users to evaluate their experiences with health services. As these evaluations are regularly contextualized with facts from users’ private lives, they often accidentally disclose personal information on the Web. This poses a serious threat to users’ privacy. In this paper, we report on early work in progress on “Text Broom”, a tool to detect privacy breaches in user-generated texts. For this purpose, we conceptualize a pipeline which combines methods of Natural Language Processing such as Named Entity Recognition, linguistic patterns and domain-specific Machine Learning approaches which have the potential to recognize privacy violations with wide coverage. A prototypical web application is openly accesible.
Keywords: Detection of Privacy Violations; Physician Reviews

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Adjusting the Structure and Electronic Properties of Carbons for Metal‐Free Carbocatalysis of Organic Transformations - Antonietti, Markus; Lopez Salas, Nieves; Primo, Ana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mimicking synaptic plasticity and learning behaviours in solution processed SnO2 memristor - Pan, Ying; Wan, Tao; Du, Haiwei; Qu, Bo; Wang, Danyang; Ha, Tae-Jun; Chu, Dewei (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Machine learning and natural language processing on the patent corpus: Data, tools, and new measures - Balsmeier, Benjamin; Assaf, Mohamad; Chesebro, Tyler; Fierro, Gabe; Johnson, Kevin; Johnson, Scott; Li, Guan‐Cheng; Lück, Sonja; O'Reagan, Doug; Yeh, Bill; Zang, Guangzheng; Fleming, Lee (Journal of Economics & Management Strategy)
Drawing upon recent advances in machine learning and natural language processing, we introduce new tools that automatically ingest, parse, disambiguate, and build an updated database using U.S. patent data. The tools identify unique inventor, assignee, and location entities mentioned on each granted U.S. patent from 1976 to 2016. We describe data flow, algorithms, user interfaces, descriptive statistics, and a novelty measure based on the first appearance of a word in the patent corpus. We illustrate an automated coinventor network mapping tool and visualize trends in patenting over the last 40 years.
Keywords: Management of Technology and Innovation; Strategy and Management; Economics and Econometrics; General Business; Management and Accounting; General Medicine

Effectuation, entrepreneurs' leadership behaviour, and employee outcomes: a conceptual model - Hubner-Benz, Sylvia; Baum, Matthias (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Internet of Things Architecture for Handling Stream Air Pollution Data - Kersting, Joschka; Geierhos, Michaela; Jung, Hanmin; Kim, Taehong (Proceedings of the 2nd International Conference on Internet of Things, Big Data and Security)
In this paper, we present an IoT architecture which handles stream sensor data of air pollution. Particle pollution is known as a serious threat to human health. Along with developments in the use of wireless sensors and the IoT, we propose an architecture that flexibly measures and processes stream data collected in real-time by movable and low-cost IoT sensors. Thus, it enables a wide-spread network of wireless sensors that can follow changes in human behavior. Apart from stating reasons for the need of such a development and its requirements, we provide a conceptual design as well as a technological design of such an architecture. The technological design consists of Kaa and Apache Storm which can collect air pollution information in real-time and solve various problems to process data such as missing data and synchronization. This enables us to add a simulation in which we provide issues that might come up when having our architecture in use. Together with these issues, we state r easons for choosing specific modules among candidates. Our architecture combines wireless sensors with the Kaa IoT framework, an Apache Kafka pipeline and an Apache Storm Data Stream Management System among others. We even provide open-government data sets that are freely available.
Keywords: Wireless Sensor Network; Internet of Things; Stream Data; Air Pollution; DSMS; Real-time Data Processing

Reciprocation Effort Games - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: interaction; reciprocation; contribute; shared effort; curbing; convergence; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Competition between Cooperative Projects - Polevoy, Gleb; de Weerdt, M.M. (Proceedings of the 29th Benelux Conference on Artificial Intelligence)
Keywords: agents; projects; contribute; shared effort game; competition; quota; threshold; Nash equilibrium; social welfare; efficiency; price of anarchy; price of stability

Predicting Early Warning Signals of Financial Distress: Theory and Empirical Evidence - Sievers, Sönke; Klobucnik, Jan; Miersch, David
This study proposes a simple theoretical framework that allows for assessing financial distress up to five years in advance. We jointly model financial distress by using two of its key driving factors: declining cash-generating ability and insufficient liquidity reserves. The model is based on stochastic processes and incorporates firm-level and industry-sector developments. A large-scale empirical implementation for US-listed firms over the period of 1980-2010 shows important improvements in the discriminatory accuracy and demonstrates incremental information content beyond state-of-the-art accounting and market-based prediction models. Consequently, this study might provide important ex ante warning signals for investors, regulators and practitioners.
Keywords: Financial distress prediction; probability of default; accounting information; stochastic processes; simulation

"A variational formulation for fuzzy analysis in continuum mechanics" - Mahnken, Rolf (Mathematics and Mechanics of complex systems)
In order to improve the credibility of modern simulation tools, uncertainties of different kinds have to be considered. This work is focused on epistemic uncertainties in the framework of continuum mechanics, which are taken into account by fuzzy analysis. The underlying min-max optimization problem of the extension principle is approximated by α-discretization, resulting in a separation of minimum and maximum problems. To become more universal, so-called quantities of interest are employed, which allow a general formulation for the target problem of interest. In this way, the relation to parameter identification problems based on least-squares functions is highlighted. The solutions of the related optimization problems with simple constraints are obtained with a gradient-based scheme, which is derived from a sensitvity analysis for the target problem by means of a variational formulation. Two numerical examples for the fuzzy analysis of material parameters are concerned with a necking problem at large strain elastoplasticity and a perforated strip at large strain hyperelasticity to demonstrate the versatility of the proposed variational formulation.
Keywords: fuzzy analysis; α-level optimization; quantities of interest; optimization with simple constraints; large strain elasticity; large strain elastoplasticity

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

Predicting Early Warning Signals of Financial Distress: Theory and Empirical Evidence - Klobucnik, Jan; Miersch, David; Sievers, Sönke (SSRN Electronic Journal)
This study proposes a simple theoretical framework that allows for assessing financial distress up to five years in advance. We jointly model financial distress by using two of its key driving factors: declining cash-generating ability and insufficient liquidity reserves. The model is based on stochastic processes and incorporates firm-level and industry-sector developments. A large-scale empirical implementation for US-listed firms over the period of 1980-2010 shows important improvements in the discriminatory accuracy and demonstrates incremental information content beyond state-of-the-art accounting and market-based prediction models. Consequently, this study might provide important ex ante warning signals for investors, regulators and practitioners.
Keywords: Financial distress prediction; probability of default; accounting information; stochastic processes; simulation

Measuring and modeling salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
For almost three decades, the theory of visual attention (TVA) has been successful in mathematically describing and explaining a wide variety of phenomena in visual selection and recognition with high quantitative precision. Interestingly, the influence of feature contrast on attention has been included in TVA only recently, although it has been extensively studied outside the TVA framework. The present approach further develops this extension of TVA’s scope by measuring and modeling salience. An empirical measure of salience is achieved by linking different (orientation and luminance) contrasts to a TVA parameter. In the modeling part, the function relating feature contrasts to salience is described mathematically and tested against alternatives by Bayesian model comparison. This model comparison reveals that the power function is an appropriate model of salience growth in the dimensions of orientation and luminance contrast. Furthermore, if contrasts from the two dimensions are comb
Keywords: Salience; Visual attention; Bayesian inference; Theory of visual attention; Computational modeling; Inference; Object Recognition; Theories; Visual Perception; Visual Attention; Luminance; Perceptual Orientation; Statistical Probability; Stimulus Salience; Computational Modeling

Accounting quality in private firms during the transition towards international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska (Accounting in Europe)
We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.  Full Article  Figures & data References  Citations Metrics  Reprints & Permissions  PDF Abstract We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.
Keywords: private firms; accounting quality; development of accounting standards; IFRS-like standards; Slovenia

Process characteristics and load-bearing capacities of joints welded with elements for the application in multi-material design - Meschut, Gerson; Schmal, Christopher; Olfermann, Thomas (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Self-locking self-pierce riveting: a new self-pierce riveting technology for multi-material applications in lightweight car body structures - Sartisson, Vadim; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Combining a high-speed mechanical joining technique with the attachment of functional elements in automotive structures - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Flow drill screwing of fibre-reinforced plastic-metal composites without a pilot hole - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, Markus; Peters, K.; Taube, Alexander; Keller, Adrian; Hoyer, Kay-Peter; Niendorf, Thomas; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Duplex stainless steel fabricated by selective laser melting - Microstructural and mechanical properties - Hengsbach, Florian; Koppa, Peter; Duschik, Kristina; Holzweissig, Martin Joachim; Burns, Madison; Nellesen, Jens; Tillmann, Wolfgang; Tröster, Thomas; Hoyer, Kay-Peter; Schaper, Mirko (Materials & Design)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

The Game of Reciprocation Habits - Polevoy, Gleb; de Weerdt, M.M.; Jonker, C.M. (Proceedings of the 2016 European Conference on Artificial Intelligence)
Keywords: agents; action; repeated reciprocation; fixed; floating; network; Nash equilibrium; social welfare; price of anarchy; price of stability; convex combination

How to Complete Customer Requirements: Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Bäumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB))
One purpose of requirement refinement is that higher-level requirements have to be translated to something usable by developers. Since customer requirements are often written in natural language by end users, they lack precision, completeness and consistency. Although user stories are often used in the requirement elicitation process in order to describe the possibilities how to interact with the software, there is always something unspoken. Here, we present techniques how to automatically refine vague software descriptions. Thus, we can bridge the gap by first revising natural language utterances from higher-level to more detailed customer requirements, before functionality matters. We therefore focus on the resolution of semantically incomplete user-generated sentences (i.e. non-instantiated arguments of predicates) and provide ontology-based gap-filling suggestions how to complete unverbalized information in the user’s demand.
Keywords: Requirement refinement; Concept expansion; Ontology-based instantiation of predicate-argument structure

Fast and conspicuous? Quantifying salience with the theory of visual attention. - Krüger, Alexander; Tünnermann, Jan; Scharlau, Ingrid (Advances in Cognitive Psychology)
Particular differences between an object and its surrounding cause salience, guide attention, and improve performance in various tasks. While much research has been dedicated to identifying which feature dimensions contribute to salience, much less regard has been paid to the quantitative strength of the salience caused by feature differences. Only a few studies systematically related salience effects to a common salience measure, and they are partly outdated in the light of new findings on the time course of salience effects. We propose Bundesen’s Theory of Visual Attention (TV A) as a theoretical basis for measuring salience and introduce an empirical and modeling approach to link this theory to data retrieved from temporal-order judgments. With this procedure, TV A becomes applicable to a broad range of salience-related stimulus material. Three experiments with orientation pop-out displays demonstrate the feasibility of the method. A 4th experiment substantiates its applicability t
Keywords: salience; visual attention; Bayesian inference; theory of visual attention; computational modeling; Visual Attention; Computational Modeling; Inference; Judgment; Statistical Probability

Peripheral visual cues: Their fate in processing and effects on attention and temporal-order perception. - Tünnermann, Jan; Scharlau, Ingrid (Frontiers in Psychology)
Peripheral visual cues lead to large shifts in psychometric distributions of temporal-order judgments. In one view, such shifts are attributed to attention speeding up processing of the cued stimulus, so-called prior entry. However, sometimes these shifts are so large that it is unlikely that they are caused by attention alone. Here we tested the prevalent alternative explanation that the cue is sometimes confused with the target on a perceptual level, bolstering the shift of the psychometric function. We applied a novel model of cued temporal-order judgments, derived from Bundesen’s Theory of Visual Attention.We found that cue–target confusions indeed contribute to shifting psychometric functions. However, cue-induced changes in the processing rates of the target stimuli play an important role, too. At smaller cueing intervals, the cue increased the processing speed of the target. At larger intervals, inhibition of return was predominant. Earlier studies of cued TOJs were insensitive
Keywords: cueing; temporal-order judgements; theory of visual attention (TVA); peripheral cue; processing speed; stimulus encoding; prior entry; Attention; Cues; Face Perception; Judgment

Mechanical properties of an innovative shear-clinching technology for ultra-high-strength steel and aluminium in lightweight car body structures - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

Theory of Knowledge for Literature Reviews: An Epistemological Model, Taxonomy and Empirical Analysis of IS Literature - Schryen, Guido; Wagner, Gerit; Benlian, Alexander (International Conference on Information Systems (ICIS))
Literature reviews play an important role in the development of knowledge. Yet, we observe a lack of theoretical underpinning of and epistemological insights into how literature reviews can contribute to knowledge creation and have actually contributed in the IS discipline. To address these theoretical and empirical research gaps, we suggest a novel epistemological model of literature reviews. This model allows us to align different contributions of literature reviews with their underlying knowledge conversions - thereby building a bridge between the previously largely unconnected fields of literature reviews and epistemology. We evaluate the appropriateness of the model by conducting an empirical analysis of 173 IS literature reviews which were published in 39 pertinent IS journals between 2000 and 2014. Based on this analysis, we derive an epistemological taxonomy of IS literature reviews, which complements previously suggested typologies.
Keywords: Literature review; Research methods/methodology; Theory of knowledge

Zum Einfluss des didaktischen Designs auf das (motivationale) Erleben von Lehrveranstaltungen: Eine quantitative Fallstudie im Rahmen der Methodeneinführung in den Bildungswissenschaften - Goller, Michael (die hochschullehre)
Im Sinne eines Scholarship of Teaching and Learning wird in diesem Aufsatz die Neugestaltung einer eigenständig durchgeführten Lehrveranstaltung im Bereich der Forschungsmethoden empirisch untersucht. Die neugestaltete Lehrveranstaltung integriert sowohl direkt-instruktionale als auch kooperativ-offene Sitzungsformate und wird mit einer thematisch ähnlichen Lehrveranstaltung des Jahres 2012 verglichen, welche fast ausschließlich im Vorlesungsstil (direkt-instruktional) gehalten wurde. Im Mittelpunkt des Evaluationsvorhabens standen folgende Forschungsfragen: (1) Unterscheiden sich die summativen Evaluationen der Lehrveranstaltungen der Jahre 2012 und 2014 in den Variablen subjektiver Lernerfolg, Motivation zur selbstständigen Auseinandersetzung mit den Inhalten sowie Gesamteindruck des Seminars?, (2) Welchen Einfluss hat die Form der Sitzungsgestaltung (direkt-instruktional vs. kooperativ-offen) auf das Erleben von Kompetenz, Autonomie und sozialer Eingebundenheit?, (3) Welche Form der Sitzungsgestaltung wird von den Studierenden stärker akzeptiert? und (4) Welchen Einfluss hat die Form der Sitzungsgestaltung auf den subjektiven Lernerfolg der Studierenden? Empirisch zeigte sich, dass die neugestaltete Lehrveranstaltung des Jahres 2014 von den Studierenden in fast allen Variablen als lernwirksamer eingeschätzt wurde. Des Weiteren ergaben sich Hinweise, dass sich kooperativ-offene Sitzungsformate positiv auf motivationale Ausgangsbedingungen auswirken.
Keywords: Direkte Instruktion; Evaluation; Kooperatives Lernen; Methodenausbildung; Paderborn; Scholarship of Teaching and Learning

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt